2019
DOI: 10.1108/ils-07-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

An iterative process for developing digital gamified sexual health education for adolescent students in low-tech settings

Abstract: Purpose Digital technology has great potential for educating today’s digitally oriented adolescents on health. In particular, digital health gamified learning can make the promotion of the sexual well-being of adolescents more effective. Although venereal diseases such as HIV/AIDS have become a greater problem in Sub-Saharan African (SSA) countries than in any country outside of Africa, little is publicly known about the development of gamified learning for use in counter-measures. This paper aims to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 33 publications
1
37
0
12
Order By: Relevance
“…The interview guide was developed based on the MAKE evaluation criteria suggested in the prior study of Haruna et al (2019aHaruna et al ( , 2019b. This MAKE evaluation instrument has four key elements: motivation, attitude, knowledge and engagement (Figure 1).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interview guide was developed based on the MAKE evaluation criteria suggested in the prior study of Haruna et al (2019aHaruna et al ( , 2019b. This MAKE evaluation instrument has four key elements: motivation, attitude, knowledge and engagement (Figure 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…Serious gamified instructions also received positive comments on motivation relative to teacher-centred learning. Previous studies indicated that creating a gamified learning system that promised to engage students' needs to consider factors of tracking points, scores, awards (badges) on the leaderboards (Haruna et al, 2019a(Haruna et al, , 2019b. This reinforced students to compete positively within a class to perform different difficult and demanding learning activities in a proactive manner, ultimately leading to contributing in their learning progress and achieving the highest level on the leaderboards, as student engagement is multidimensional aspects that involve three aspects (Fredricks et al, 2004).…”
Section: Enhancing Instructional Outcomesmentioning
confidence: 99%
“…Previous research has shown that theoretical models such as the health belief model show promise as theoretical frameworks for understanding for vaccine uptake among young adult males living in urban settings [ 24 ]. Our study clarifies the broader relationships between multiple theories and constructs (including the health belief model) that can be used to measure the impact of gaming on individuals, particularly for educating this population on the importance of HPV [ 18 ].…”
Section: Discussionmentioning
confidence: 81%
“…However, this game was not theory-based and is only meant to increase awareness and knowledge of HPV. A game that is developed as a health intervention must have the ability to be appropriately evaluated and engaging [ 18 ]. In the absence of standardized evaluation methods for serious games, design principles (ie, usability, playability, and visualization) are incorporated into designing a gameplay experience that does not distract the user from the intended outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several methods of health education regarding adolescent reproductive health have been developed, including lectures and discussions, focus group discussions, games and peer groups (Ambrose, 17 C.E. ; Haruna et al, 2018Haruna et al, , 2019Nyumba, 2018). Meanwhile, one of the health education methods that we would like to highlight here is a method that uses the snake and ladder playing technique.…”
mentioning
confidence: 99%